FACULTY PERCEPTION TOWARD ONLINE EDUCATION DURING THE COVID-19 PANDEMIC - Dahal , Sailaza; Dahal , Samipa; Pokharel , Bibhor (Journal of Chitwan Medical College, 2022)
Background: COVID-19 outbreak has changed the education system from traditional classroom to online education across the world. Due to need for social distancing, countries were bound to close the educational institutions and adapt online learning as the only means available for learning. Although, this has provided teachers an opportunity to work from home, at the same time it has brought many challenges. Therefore, understanding faculty perception is an important aspect for successful implementation of online education. Thus, this study aimed to identify the faculty perception toward online education during COVID-19 pandemic. Methods: Cross-sectional online survey was conducted from December 2020 to September 2021 during both the 1st and 2nd wave of COVID-19 Pandemic and lockdown in Nepal. Convenience sampling was used to select the faculty members from different universities across different places of Nepal. Self-developed five-point Likert scale was used to assess faculty perception toward online education. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 16 using statistical tool like frequency, percentage, mean and standard deviation. Results: Total 394 faculty members participated in the study. More than half 271 (68.8%) of the respondents had positive perception, whereas, only 123 (31.2%) had negative perception toward online education. The mean score of perception of was 3.14±0.279. Conclusions: More than half of the faculty had positive perception toward online education, which concludes that, online education can be an effective means of continuing education during the crisis situations like COVID-19 pandemic. However, the finding of this study offers useful suggestion for policy makers and stake holders to develop proper strategies and on-going professional development courses and training programs to successfully implement online education program.